Bangladesh in India's maritime strategy towards the Bay of Bengal: Towards a comprehensive Indo-Pacific outlook. (3rd July 2022) - Haldar, Sayantan
ABSTRACT: This article looks at the potential of Bangladesh in India's maritime strategy in the Bay of Bengal, in light of the shifting focus on the emergent Indo-Pacific. It argues that India's maritime strategy in the Bay of Bengal is a driver of its wider engagement in the emerging Indo-Pacific. Therefore, engaging Bangladesh in the Bay of Bengal is strategically imperative for India. However, this requires New Delhi to deepen and expand its strategic convergences with Bangladesh and ensure that Dhaka warms up to the idea of an emergent Indo-Pacific that might even prompt geopolitical and geo-strategic competition with China.